Therapeutic Hypothermia in Children and Adults with Severe Traumatic Brain Injury - Sandestig, Anna (Mary Ann Liebert, Inc., 2014)
Great expectations have been raised about neuroprotection of therapeutic hypothermia in patients with traumatic brain injury (TBI) by analogy with its effects after heart arrest, neonatal asphyxia, and drowning in cold water. The aim of this study is to review our present knowledge of the effect of therapeutic hypothermia on outcome in children and adults with severe TBI. A literature search for relevant articles in English published from year 2000 up to December 2013 found 19 studies. No signs of improvement in outcome from hypothermia were seen in the five pediatric studies. Varied results were reported in 14 studies on adult patients, 2 of which reported a tendency of higher mortality and worse neurological outcome, 4 reported lower mortality, and 9 reported favorable neurological outcome with hypothermia. The quality of several trials was low. The best-performed randomized studies showed no improvement in outcome by hypothermia—some even indicated worse outcome. TBI patients may suffer from hypothermia-induced pulmonary and coagulation side effects, from side effects of vasopressors when re-establishing the hypothermia-induced lowered blood pressure, and from a rebound increase in intracranial pressure (ICP) during and after rewarming. The difference between body temperature and temperature set by the biological thermostat may cause stress-induced worsening of the circulation and oxygenation in injured areas of the brain. These mechanisms may counteract neuroprotective effects of therapeutic hypothermia. We conclude that we still lack scientific support as a first-tier therapy for the use of therapeutic hypothermia in TBI patients for both adults and children, but it may still be an option as a second-tier therapy for refractory intracranial hypertension.